2010
DOI: 10.3390/md8030471
|View full text |Cite
|
Sign up to set email alerts
|

Primary Screening of the Bioactivity of Brackishwater Cyanobacteria: Toxicity of Crude Extracts to Artemia salina Larvae and Paracentrotus lividus Embryos

Abstract: Cyanobacteria are a diverse group of Gram-negative bacteria that produce an array of secondary compounds with selective bioactivity against vertebrates, invertebrates, plants, microalgae, fungi, bacteria, viruses and cell lines. The aim of this study was to assess the toxic effects of aqueous, methanolic and hexane crude extracts of benthic and picoplanktonic cyanobacteria isolated from estuarine environments, towards the nauplii of the brine shrimp Artemia salina and embryos of the sea urchin Paracentrotus li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 20 publications
0
24
1
2
Order By: Relevance
“…Neurotoxic and hepatotoxic effects as well antialgal, immunosuppressive, antimycotic, antibacterial, antitumour and antiviral activity have been described ( Gademann and Portmann, 2008, Hirata et al, 2003, Jaiswal et al, 2008, Martins et al, 2007, Martins et al, 2008, Mundt et al, 2001and Wiegand and Pflugmacher, 2005. On the other hand, recent studies have already demonstrated that cyanobacteria isolated from estuaries induce toxic effects on marine invertebrates ( Lopes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Neurotoxic and hepatotoxic effects as well antialgal, immunosuppressive, antimycotic, antibacterial, antitumour and antiviral activity have been described ( Gademann and Portmann, 2008, Hirata et al, 2003, Jaiswal et al, 2008, Martins et al, 2007, Martins et al, 2008, Mundt et al, 2001and Wiegand and Pflugmacher, 2005. On the other hand, recent studies have already demonstrated that cyanobacteria isolated from estuaries induce toxic effects on marine invertebrates ( Lopes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence of anabaenopeptins A and D in a benthic brackish-water Nostoc isolate from an Atlantic estuary (Minho River, Portugal) has been reported by Lopes and co-workers (unpublished information). Moreover, Lopes et al (2010) and have shown that benthic cyanobacteria from Atlantic estuaries (e.g. Synechococcus,…”
Section: Further Cyanotoxinsmentioning
confidence: 99%
“…E-mail: vmvascon@ fc.up.pt Tan, 2007). The cyanobacteria of brackish waters (including estuaries), however, remain under-investigated, particularly in Europe, despite a number of significant contributions (Sivonen et al, 1989;Nehring, 1993;Lehtima¨ki et al, 1994Lehtima¨ki et al, , 1997Lehtima¨ki et al, , 2000Wille´n & Mattson, 1997;Sivonen & Jones, 1999;Sipia¨et al, 2001Sipia¨et al, , 2002Sipia¨et al, , 2006Sipia¨et al, , 2007Sipia¨et al, , 2008Vasconcelos & Cerqueira, 2001;Laamanen et al, 2002;Rocha et al, 2002;Geiss et al, 2003;Hobson & Fallowfield, 2003;Lehtonen et al, 2003;Stal et al, 2003;Sobrino et al, 2004;Herfindal et al, 2005;Kankaanpa¨a¨et al, 2005;Karjalainen et al, 2005Karjalainen et al, , 2007Karlsson et al, 2005;Pere´z & Carrilo, 2005;Surakka et al, 2005;Marino et al, 2006;Mazur-Marzec et al, 2007Paoli et al, 2007;Halinen et al, 2008;Ibelings & Havens, 2008;Jo´z´wiak et al, 2008;Lopes et al, 2010;Oftedal et al, 2010;). This lack of information for brackish-water cyanobacteria is especially significant in relation to the potential for production of new bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Nonaxenic and uni-cyanobacterial cultures were posteriorly lyophilized. The taxonomic characterization was performed as described before by Lopes et al (2010).…”
Section: Cyanobacteria Isolation and Culturementioning
confidence: 99%
“…Trichloroacetic acid (TCA), Methanol/Acetone and hydrochloric acid (HCl) have been evaluated to extract BMAA from cyanobacterial samples (Banack et al 2007;Eriksson et al 2009). Samples were collected and made unialgal by the standard methods (Lopes et al 2010). Eighteen different strains were analyzed for the presence of BMAA, in what, as far as we know, is the first report of BMAA presence in estuaries.…”
Section: Introductionmentioning
confidence: 99%